Development of anti-icing coatings for sports application - Wu, Xinghua (2019)
Undesired ice accumulation on outdoor sports facilities leads to severe economic issues and even loss of lives. Great efforts have been made to fabricate ice prevention surfaces or facilities since 1800s. The utilized methods can be categorized into four types: mechanical methods, chemical methods, thermal methods and combined methods (combing two or three former referred methods). Considering the economic impact and additional labour burdens, chemical methods are commonly adopted and widely studied. To avoid numerous environmental effect of drain-off chemicals, icephobic coatings, as effective passive anti-icing methods, have attracted much attention in recent decades. However, less attention has been paid on development of the anti-icing coatings for sports facilities and other related applications that requires additional properties including mechanical durability, transparency, easy processability and so on. With expectation to repel incoming water before ice formation, superhydrophobic coatings that exhibit superior water repellency and bouncy effect, have been widely studied since 1997. However, not all superhydrophobic coatings present anti-icing behaviours due to water condensation. This study begins with the investigation of the effect of water condensation on superhydrophobic coatings with different microstructures. To design superhydrophobic coatings with different microstructures, a sol-gel method was employed with adjustment of the weight ratio of nanoparticles with different surface energies. One of the prepared coatings demonstrated robust icephobicity with low ice-adhesion strength of ~ 60 kPa under water condensation conditions; at the same time, it also displayed a low ice-nucleation temperature of ~-26 degree celsius and low icing probability.